Viral Disruption of Blood–Testis Barrier Precedes Testicular Infection - E. Eldridge Hager-Soto; Alexander N. Freiberg; Shannan L. Rossi (Viruses)
Several viruses have demonstrated the potential for infecting the human male genital tract, leading to potential host pathologic consequences and sexual transmission. Despite the testes being an immune-privileged niche of the body, viruses like Zika, mumps, Ebola, Marburg, and human immunodeficiency virus infect the lumen of testes. The human blood–testis barrier (BTB) is a specialized epithelial barrier responsible for protecting the developing sperm in the lumen of the seminiferous tubules from foreign antigen; however, testicular-tropic viruses possess the unique ability to modulate this barrier prior to entry into the lumen. Previous scientific reports identified immunomodulatory and viral-induced changes to BTB physiology during infection—a necessary step prior to viral entry into the testicular lumen. This review aims to explore the specific mechanisms employed by viruses to disrupt the human BTB and establish testicular infection.